Impact of guidance on intervention adherence in computerised interventions for mental health problems: a meta-analysis. Issue 2 (22nd January 2022) - Musiat, Peter; Johnson, Catherine; Atkinson, Melissa; Wilksch, Simon; Wade, Tracey
Abstract: Web-based interventions are increasingly used for the prevention, treatment and aftercare of mental disorders. A crucial factor to the efficacy of such online programmes is adherence to the intervention content and procedure. It has been frequently suggested that adherence in web-based interventions is low and little is known about which factors influence adherence. To increase intervention uptake and completion, studies increasingly include interventions with some form of guidance. Guided interventions have been shown to have higher efficacy, however, evidence for the impact on adherence is limited and mixed. This meta-analysis explored the impact of human guidance on intervention completion in web-based mental health interventions. A total of 22 studies were included with interventions primarily targeting symptoms of depression and anxiety disorders. Results showed that guidance significantly increases the average amount of intervention completion [ g = 0.29, 95% confidence interval (CI) 0.18–0.40] and the proportion of intervention completers [ log odds ratio (OR) = 0.50, 95% CI 0.34–0.66] with small effects. On average, full completion rates were 12% higher in guided intervention groups. This meta-analysis demonstrated that guidance in web-based mental health interventions does increase adherence, but more research is required to better understand the specific mechanisms between guidance, adherence and outcomes.